Parasite spatial distribution shapes parasite aggregation on host populations, but not at high parasite density - Chris Wojan; Allison K. Shaw; Meggan E. Craft (Ecosphere)
Abstract Spatial aggregation of environmental or trophically transmitted parasites has the potential to influence host–parasite interactions. The distribution of parasites on hosts is one result of those interactions, and the role of spatial aggregation is unclear. We use a spatially explicit agent‐based model to determine how spatial aggregation of parasites influences the distribution of parasite burdens across a range of parasite densities and host recovery rates. Our model simulates the random movement of hosts across landscapes with varying spatial configurations of areas occupied by environmental parasites, allowing hosts to acquire parasites they encounter and subsequently lose them. When parasites are more spatially aggregated in the environment, the aggregation of parasite burdens on hosts is higher (i.e., more hosts with few parasites, fewer hosts with many parasites), but the effect is less pronounced at high parasite density and fast host recovery rates. In addition, the correlation between individual hosts' final parasite burdens and their cumulative parasite burdens (including lost parasites) is greater at higher levels of spatial parasite aggregation. Our work suggests that fine‐scale spatial patterns of parasites can play a strong role in shaping how hosts are parasitized, particularly when parasite density is low‐to‐moderate and recovery rates are slow.